The effect of service quality on saving decisions with Islamic branding as a moderating variable - Fitria Magdalena Suprapto (Journal of Islamic Economics, Management, and Business (JIEMB), 2021)
Purpose-This study aims to examine the effect of service quality on saving decisions with Islamic branding as a moderating variable.Method–The research sample was 100 respondents. The data collection technique used a questionnaire distributed at the cross-sectional time. Statistical testing of research data using PLS-based Structural Equation Modeling.Results–The first hypothesis is stated to be supported, namely the service quality variable has a significant positive effect on saving decisions. The second hypothesis is that the Islamic branding variable moderates the relationship between service quality and saving decisions.Implication–The results of this study can assist business actors in improving the service quality.Originality–This study is the first study to discuss Islamic branding as a moderating variable between service quality and saving decisions.